2008
DOI: 10.1093/jat/32.7.505
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Among Plasma, Serum, and Whole Blood Ethanol Concentrations: Impact of Storage Conditions and Collection Tubes

Abstract: How blood samples are processed and stored before being analyzed for alcohol levels is of concern in the forensic and toxicological fields, and is important in the standardization of research methods. This experiment explored for systematic differences in ethanol levels among several methods of processing and storing blood samples. Five adults consumed a standard alcoholic drink (0.7 g/kg) over a 15-min period, and blood samples were taken 5 times during a 3-h period following drinking onset. Samples for plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…One study showed that inclusion of fluoride ions made no difference when the tubes were refrigerated or kept at room temperature for 14 days before analysis [18] . This was confirmed in another study when the blood specimens were stored for 10 days [19] . The need for 100 mg NaF in ante-mortem forensic blood samples seems more of a historical tradition rather than a proven necessity.…”
Section: Discussionsupporting
confidence: 54%
“…One study showed that inclusion of fluoride ions made no difference when the tubes were refrigerated or kept at room temperature for 14 days before analysis [18] . This was confirmed in another study when the blood specimens were stored for 10 days [19] . The need for 100 mg NaF in ante-mortem forensic blood samples seems more of a historical tradition rather than a proven necessity.…”
Section: Discussionsupporting
confidence: 54%
“…The blood samples were then centrifuged, and the plasma separated into a plastic vial. Quantitative analysis of ethanol levels was performed by gas chromatography with flame ionization detection (GC ⁄ FID) (Hewlett-Packard model 5890 series II equipped with a model 18593B autosampler) (Penetar et al, 2008). Analysis was performed on every 5-minute sample after the commencement of drinking for 75 minutes and on samples taken at 90, 120, 150, and 180 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…7 Whole blood, on average, will give a lower ethanol result than the use of serum (reported at 11% lower). 8 Additionally, the observed negative bias may be attributed to systemic bias related to differences in calibration between the two methods. In this cohort of specimens there are three serum specimens that were analyzed by the SDCMEO and the hospitals.…”
Section: Resultsmentioning
confidence: 99%